Acute heat stress during transportation deteriorated the qualities of rainbow trout (Oncorhynchus mykiss) fillets during chilling storage and its relief attempt by ascorbic acid. (15th February 2022) - Zhao, Manman; You, Xiaopeng; Wu, Yiwen; Wang, Lan; Wu, Wenjin; Shi, Liu; Sun, Weiqing; Xiong, Guangquan
Abstract: The work was to investigate the impacts of acute heat stress during transportation on the tissue structure, physicochemical and microbial qualities of rainbow trout ( Oncorhynchus mykiss ) fillets during chilling storage and its relief attempt by ascorbic acid. Different transportation groups were performed: transported samples under controlled temperature, T1; transported samples without temperature control, T2; and transported samples with the addition of 30 mg L-1 ascorbic acid, T3. Rainbow trout without transportation were set as the control. In comparison with non-heat stress treatment (control and T1 group), the acute heat stress (T2 and T3 group) significantly increased the relaxation time of free water (T22 ), total volatile basic nitrogen (TVB-N) and malondialdehyde (MDA) content, total viable count (TVC) and K value of fillets during chilling storage. T3 group had tissue with relative integrity cell shapes and lower expressible moisture (0–3 d), TVB-N and MDA content and TVC (0–7 d) compared with acute heat stress group (T2 group). Therefore, acute heat stress during transportation accelerated the quality deterioration of fillets during the storage, and treatment of control water temperature or the addition of ascorbic acid partially relieved the damage caused by acute heat stress. Highlights: Acute heat stress during transportation damaged the quality of rainbow trout fillets. Transportation in 16.5 °C decreased TVB-N content and TVC of fillets during storage. Addition Vc partially relieved the acute heat stress damage of fillets during storage. Transportation in 16.5 °C or addition Vc extended the shelf life of fillets by 2 d.